Perioperative opioid management for minimally invasive hysterectomy. (December 2022) - Madsen, Annetta M.; Martin, Jessica M.; Linder, Brian J.; Gebhart, John B.
Abstract: Given the high volume of hysterectomies performed, the contribution of gynecologists to the opioid crisis is potentially significant. Following a hysterectomy, most patients are over-prescribed opioids, are vulnerable to developing new persistent opioid use, and can be the source of misuse, diversion, or accidental exposure. People who misuse opioids are at risk of an overdose related death, which is now one of the leading causes of death in the United States and is rising in other countries. It is the physician's responsibility to reduce opioid use by making impactful practice changes, such as 1) using pre-emptive opioid sparing strategies, 2) optimizing multimodal nonopioid pain management, 3) restricting postoperative opioid prescribing, and 4) educating patients on proper disposal of unused opioids. These changes can be implemented with an enhanced recovery after surgery protocol, shared decision-making, and patient education strategies related to opioids. Highlights: Postoperative opioid prescribing significantly contributes to the opioid epidemic. Preoperative education and shared decision-making can reduce postoperative opioid use. Non-opioid multimodal pain management can significantly reduce opioid use. Individualized restrictive prescribing decreases the volume of leftover opioid pills. Patient education on disposal is critical to prevent opioid misuse and diversion.